Eksplorasi Etnomatematika Pada Alat Musik Pantun Bambu Cilegon - Deslianti Uliarta Pasaribu; Sukirwan (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
Ethnomathematics is an activity carried out by cultural groups without realizing that there are basic mathematical concepts in their application. Ethnomathematics as a study of mathematics with cultural nuances will contribute to the field of education. This study aims to explore the mathematical concept of the musical instrument Pantun Bambu Cilegon City. This study uses descriptive qualitative research with ethnographic method. This research was conducted at Sanggar Singpring, Link. Temugiring, Kel.Banjarnegara, Kec.Ciwandan, Cilegon City, Banten. The subjects in this study were Mr. Afandi, Mr. Iing, and Mr. Imadudin. Data were collected by conducting interviews, observation, and documentation. Data analysis uses data collection, data reduction, data presentation, and conclusions. The results showed that there are mathematical concepts in Pantun Bambu, namely plane geometry, solid geometry, and arithmetic sequences. The results of this study are expected to help in the field of education, especially mathematics in understanding mathematical concepts because it is associated with the cultural life around it. Keywords: Exploration, Ethnomathematics, Pantun Bambu